Childhood : great expectations - Edelman, Marian Wright; Hinde, Robert A.; Konner, Melvin; Scarr, Sandra; Bronfenbrenner, Urie, 1917-2005.; Kagan, Jerome; Chadwick, Alex, 1947-; Neary, Lynn.; Whelan, Michael; Silk, Lawrence; Akuginow, Erna.; Haines-Stiles, Geoffrey; et al. (New York, NY : Ambrose Video Publishing, Inc., 1991)
Introduces the seven-part series which explores the influences of nature and society on 12 families on five continents. Includes three births, in Russia, the United States, and Brazil, to show how different societies approach this universal, yet unique, experience.
Documentary.
Narrators: Alex Chadwick, Lynn Neary.
Director/producer/writer, Geoff Haines-Stiles; series producer/Unit Production manager, Erna Akuginow ; edited by Lawrence Silk ; music composed and performed by Michael Whelan ; advisors, Jerome Kagan, Urie Bronfenbrenner, Sandra Scarr, Melvin Konner, Robert A. Hinde, Marian Wright Edelman.
VHS.
Keywords: Child development -- Cross-cultural studies; Childbirth; Socialization; Families; Documentary films; Children